Kinerja Keuangan Perbankan Syariah: Peran Lingkungan Eksternal, Sumber Daya dan Strategi - Suganda, Uce Karna; Rachmawati, Mariana; Kurniawan, Ryan (Magister Akuntansi Universitas Pancasila, 2023)
This research aims to determine the influence of external environmental forces, company resources, and competitive strategy on the performance of the BJB Syariah Bandung banking business. The research method used is the explanatory method. The sample used was 99 BJB Syariah Bandung offices in West Java. The data analysis technique used is multiple linear regression analysis. The research results show that the strength of the external environment, company resources, and competitive strategies as well as banking financial performance are in